Isothermal Modelling of the Adsorption of Malachite Green onto Rice husks (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
The rice milling process produces rice husks as a by-product. It is one of the most important agricultural leftovers in terms of volume. The data of the sorption isotherm of Malachite Green sorption onto rice husks, which was plotted using linearized plots of isothermal models were reanalyzed using twenty isothermal models using nonlinear regression. Nineteen models — Henry, Langmuir, Freundlich, Jovanovic, Redlich-Peterson, Sips, Toth, Hill, Khan, BET, Vieth-Sladek, Radke-Prausnitz, Fritz-Schlunder III, Unilan, Baudu, Marczewski-Jaroniec,  Fritz-Schluender IV, Weber-van Vliet and Fritz-Schluender V – fitted the data best using non-linear regression. Statistical analysis based on error function analyses such as root-mean-square error (RMSE), adjusted coefficient  of determination  (adjR2),  accuracy factor (AF),  bias  factor  (BF), Bayesian Information Criterion (BIC), corrected AICc (Akaike Information Criterion), and Hannan-Quinn Criterion (HQC) showed that the best isotherm model was found to be the Redlich-Petersen with the lowest RMSE and AF, BF and adjR2 values closest to unity and lowest BIC, HQC and AICc values followed (descending order) by Jovanovic, Langmuir, Henry and Freundlich. The maximal adsorption capacity in the Jovanovic model will be used for comparative purposes since the Redlich-Petersen model does not feature a similar parameter. The  maximal adsorption capacity expressed in milligrams per gram (mg/g), for the Jovanovic model, denoted by qmJ and Kj-the Jovanovic constant, showed the calculated values of 4.04 mg/L (95% confidence interval; 3.306 to 4.773) and 0.445 (95% confidence interval; 0.264 to 0.627), respectively. The nonlinear regression method provides parameter values within the 95% confidence interval, facilitating improved comparability with prior research.
Keywords: Biosorption; Malachite Green; Isotherm; Modified rice husks; Jovanovic isotherm